Implementation of Cat and Mouse Game in Improving Locomotor Skills of Grade IV Elementary School Students - Rezka Adela Ramadhani; Ayi Suherman; Encep Sudirjo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to improve the locomotor skills of fourth grade elementary school students through the implementation of the traditional game "cat-mouse". The study used the Classroom Action Research (CAR) method which was carried out in three cycles, including planning, implementation, observation, and reflection. The subjects of the study were 20 fourth grade students of Cilengkrang Elementary School, North Sumedang Regency, consisting of 10 males and 10 females. Data collection was carried out through observation, locomotor ability tests, and teacher performance assessment instruments. The results showed a significant increase in students' locomotor abilities, with the percentage of learning completion from 30% in the pre-cycle to 85% in cycle III. In addition, teacher performance in planning and implementing learning also increased to reach the target in cycle III. The "cat-mouse" game has proven to be effective as a learning medium in improving locomotor abilities and motivating students to actively participate in physical activities.